(untitled) (AYUSHDHARA, 2022)
The menopause is permanent cessation of menstruation at the end of reproductive life due to loss of ovarian follicular activity. Shatavaryadi Churna and Guduchyadi Churna– both drugs are 6grams twice daily before meal with milk for 2 months in two groups has been given. Both are effective in the management of Postmenopausal Syndrome. Shatavaryadi Churna is more effective than Guduchyadi Churna in the management of Postmenopausal Syndrome but both are an effective, safe, promising and cost effective remedy. Vata-Pittashamaka, Rasayana, Dhatuvardhaka, Agnidipaka, Pachana, Medhya, Vedanasthapana, Hridya, Anidranash drug in Shatavaryadi Churna helped to deliver such promising results. Guduchyadi Churna had also delivered satisfactory results treating in Postmenopausal Syndrome due toits Tridoshahara & Vata-Kaphashamaka activity along with Rasayana, Dipana, Pachana, Dhatuvardhaka, Balya, Hridya, Nidrajanana, Medhya and Vedanasthapana properties. The age at menopause appears to be genetically determined and is unaffected by race, socioeconomic status, age at menarche, or number of prior ovulations. Factors that are toxic to the ovary often result in an earlier age of menopause; for e.g., who smoke experience an earlier menopause. Women who have had surgery on their ovaries, have had a hysterectomy, despite retention of their ovaries, may also experience early menopause